A função social da leitura da literatura infantil The social function of childish literature reading - Clarice Fortkamp Caldin (Encontros Bibli)
The secularism of literature, established with the Romanticism, makes a change on the reading conception. And, since this change, the reading apprenticeship, changed on social exercise and serving to legitimation of bourgeoisie, makes possible the child emancipation and the assimilation of the society values. On the childish literature beginning, it had a former function, showing models of conduct to reinforce the social values of that time. The contemporaneous childish literature gives a new conception of written scrip, open to a multiplicity of reading, questions and reflections. The school library has a relevant paper to awake the liking of childish literature reading. The librarian that knows the figure of educator, gives priority to reading of quality scripts that develop the child criticism capacity. A laicização da literatura, instalada com o Romantismo, muda a concepção da leitura. A aprendizagem da leitura, transformada em prática social e servindo de legitimação da burguesia, possibilita a emancipação da criança e a assimilação dos valores da sociedade. Nos seus primórdios, a literatura infantil tem função formadora, ao apresentar modelos de comportamento com a finalidade de reforçar os valores sociais vigentes. A literatura infantil contemporânea oferece uma nova concepção de texto escrito, aberto a múltiplas leituras, questionamentos e reflexões. A biblioteca escolar desempenha um papel relevante no despertar o gosto pela leitura da literatura infantil. O bibliotecário, consciente de sua função de educador, prioriza a leitura de textos de qualidade que desenvolvam a capacidade crítica da criança.